When Confucius "encounters" John Dewey : a cross-cultural inquiry into Dewey's visit to China - Yang, James Zhixiang (Current perspectives on Confucianism, Taoism, Buddhism, and education., 2024)
"John Dewey's sojourn to China created a historical moment between the United States and China. Therefore, some of the recent scholarship on the topic aims to uncover the social and historical implications behind Dewey's Chinese trip, centering on how intercultural conversations occurred between "Confucius" and "John Dewey" during the period of May Fourth/New Culture Movement. Much research also reflects an attempt to synthesize and unify Western and Eastern education. This book spotlights a cross-cultural "encounter" between Confucius and John Dewey by studying the four well-known Chinese scholars Hu Shih, Liang Shuming, Tao Xingzhi, and Jiang Menglin, who exerted a profound impact on many aspects of Chinese society during the May Fourth/New Culture Movement period. The study explores answers to a crucial question: What motivated Dewey's Chinese disciples to forge a synthesis of Confucian traditions and Deweyan ideas to purse of the goals of Chinese educational and cultural reformation? Simultaneously, based on an in-depth historical, philosophical, and cultural analysis of Dewey's visit to China, this study aims to disclose how our education has evolved in the context of cultural pluralism The book seeks to contribute provocative ideas to today's educators: any school of thought can renew and update itself if it maintains an open dialogue with a different civilization. Dynamic and transparent intercultural communication enables us to develop a sense of understanding and respect for cultural diversity, all of which are of great benefit to the construction of a stable and healthy international order"--